THE COMPETITIVE ANALYSIS - THE APPROPRIATE INSTRUMENT TOWARDS A SUCCESSFUL DEVELOPMENT - Pulaj (Brakaj), Enida; Kume, Vasilika (European Scientific Journal, ESJ, 2013)
Albania is a country with a long period of economic and social transition. To many industries are growing during this period. So, the relationship between competition and challenges for a sustainable growth of firms remains a basic argument for development of policies, strategies and adapting to strategic changes. Today’s competitive situation among companies, characterized by globalization, and the need to survive has lead to an urgent need for competitiveness management. The concept of competitiveness is an important element in the debate on the performance of nations, industries and firms. Also, it is vital for industries and companies to increase the knowledge and understanding of competitiveness. In order to formulate strategies for competitiveness, managers need to know what are the competitive strategies they have to use, which are the variables that affect the expected results, how are they correlate each other. In order to be able, to adapt and develop within an industry, companies have to build the appropriate infrastructure through which it is possible to understand and measure the indicators such as attractiveness of the industry, competitive rivalry, industry positioning and strategic choices. The principal aim of this paper is to make an evaluation and to analyze the issues concerning the competiveness conception. The paper is structured in two main parts related with: Understanding the competitive analysis and Strategic choices that companies use to be successful. According the purpose of this work there are following the description and comparative methods.